решить, , . b a+b_______ — ____________a-b² b²-ab

Помогите решить, пожалуйста , срочно.

 

b                        a+b

_______     -     ____________

(a-b)²                b²-ab

  •    b                        a+b                        

    _______     -     ____________  = 

    (a-b)²                   b²-ab

     

           b                        a+b                  b                        a+b

    = _______     -     ____________    =  _______    +     ____________    =

        (a-b)²                   b(b - a)            (a-b)²                     b(a  - b )

     

          b²     +    ( a + b)(a  - b )               b²    +      a²   - b²                            a²

    = __________________________    =  _______________________    =  ________

                 b(a - b)²                                        b(a - b)²                                  b(a - b)²   

  • (b*b+(a+b)*(a-b))/(b(a-b)²)=

    (b*b+a*a-b*b)/(b(a-b)*(a+b))=

    a*a/(b(a-b)²)